Antimicrobial Activity of Nostoc calcicola (Cyanobacteria) Isolated from Central India Against Human Pathogens - Agrawal, Manish Kumar (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: We have earlier shown that cyanobacteria isolated from Central India possess wide spectrum antibacterial activity. The aim of the study was to add more authenticity by preparing axenic culture of one of the cyanobacteria and to identify the cyanobacterium; Nostoc calcicola using 16s rDNA with detailed antibacterial and antifungal activities in a dose-dependent manner. Materials and Methods: A local isolate of Nostoc was grown in the laboratory and identified as N. calcicola using molecular techniques. The cells were extracted with absolute ethanol. Antimicrobial tests were performed by standard methods against five human pathogenic bacteria and four fungi. The data are presented as a mean ± standard deviation for inhibition zones. For statistical analysis, unpaired t-test was used using Sigma Graph Pad Prism® version 6.0. Results and Discussion: The results concluded that ethanolic extract of N. calcicola inhibited all the tested bacteria and fungi. The antimicrobial potency on dry weight basis (5 μg equivalent dry weight in most cases) was better than the 100 μg pure ampicillin and 30 μg miconazole. The activity was pronounced against Staphylococcus aureus ATCC 25923 and Candida albicans ATCC 10231. The active compound was stable for 6 months at 2-8°C. Conclusion: Cyanobacterial antimicrobial compounds being structurally different may have different mechanisms of action and hence can be used as a source of antibiotics and antifungal compounds for various diseases.